2023
DOI: 10.3390/brainsci13071095
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Paresthesia and the Presence of Cardiac Dysautonomia in Patients with Post-COVID-19 Syndrome: A Preliminary Observational Study

Abstract: Introduction: Post-Coronavirus disease 2019 (Post-COVID-19) syndrome has neurological symptoms related to the dysfunction of the autonomous nerve system. However, a pathogenic relationship between post-COVID-19 syndrome and dysautonomia still remains to be demonstrated. Establishing a pathogenic relationship between paresthesia and the presence of cardiac dysautonomia in patients with post-COVID-19 syndrome is the objective of this study. Participants and Methods: This observational study was carried out in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…A decrease in PNS activity (HRV parameters decreased) [22][23][24][25][26] or PNS overtones (HRV parameters increased) 20,27 in individuals with a history of COVID-19 compared to healthy individuals was previously investigated; however, they focused on the elderly or patients with severe forms of COVID-19. In this study, we reported no difference in measures of HRV in adults who had a history of SARS-CoV-2 infection compared to healthy individuals, which may be due to the fact that the majority of the sample were young adults, in line with the studies of Skow et al 28 , Buchhorn et al 29 , Freire et al 30 and López-Galán et al 31 .…”
Section: Discussionsupporting
confidence: 88%
“…A decrease in PNS activity (HRV parameters decreased) [22][23][24][25][26] or PNS overtones (HRV parameters increased) 20,27 in individuals with a history of COVID-19 compared to healthy individuals was previously investigated; however, they focused on the elderly or patients with severe forms of COVID-19. In this study, we reported no difference in measures of HRV in adults who had a history of SARS-CoV-2 infection compared to healthy individuals, which may be due to the fact that the majority of the sample were young adults, in line with the studies of Skow et al 28 , Buchhorn et al 29 , Freire et al 30 and López-Galán et al 31 .…”
Section: Discussionsupporting
confidence: 88%